Study of the Effect of Booklet Website Assisted-Game-Based Learning on Students' Motivation and Learning Outcomes in Biology Learning - Amdah, Amdah; Kurniyati, Intan; Nafsiana, Gina; Nurfadilah, Silvi; Mualifah, Anif; Sari, Sandi Danar Cynthia; Nur’aini, Devi Ayu (International Journal of Biology Education Towards Sustainable Development, 2025)
The significance of this study is to investigate the efficiency of the Blooket platform in acting as a game-based learning tool in enhancing the motivation and outcomes of students learning biology. The approach adopted for this study is a literature approach involving the exploration of various articles and findings related to the topic. From the analysis above, it is evident that the platform has vital attributes of a game-based platform. The attributes include an interactive platform design that has proven effective in boosting student engagement and motivation and increasing student understanding. The findings of various researches indicate a significant improvement in students’ motivation and active engagement and improvement in students’ understanding and achieving mastery levels in understanding biological concepts. The platform is also valid and effective as a means of evaluation and concept reinforcement. It should be noted that for successful implementation of the platform within the school curriculum, valid educational policies and teacher capacity as well as sufficient technological resources are fundamental. The use of the Blooket learning platform has proved to offer a significant and more interactive and effective means of student learning.